2005
DOI: 10.1177/070674370505000108
|View full text |Cite
|
Sign up to set email alerts
|

Panic-Agoraphobic Spectrum and Light Sensitivity in a General Population Sample in Italy

Abstract: Objective: This study aimed to verify a possible correlation between panic symptoms and photosensitivity, not only in panic disorder (PD) but also in the panic-agoraphobic spectrum. Method:One hundred and sixty-nine healthy and drug-free subjects completed the Structured Clinical Interview for Panic-Agoraphobic Spectrum-Lifetime version (SCI-PAS-Lifetime) and the Photosensitivity Assessment Questionnaire (PAQ). Results:The SCI-PAS-Lifetime total score was positively correlated with the total score of the PAQ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…This finding is consistent with the reports in literature that patients with panic disorder may exaggerate their symptoms, display tricky behaviors and pretend in order to have reassurance they need (30). It may be observed that these patients seek reassurance by frequently administering to emergency departments, running medical tests and establishing "friendship relationships" with physicians (30,43). Many patients with panic disorder ask for help from their friends, families, neighbors and physicians in order to deal with the feelings of insecurity.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is consistent with the reports in literature that patients with panic disorder may exaggerate their symptoms, display tricky behaviors and pretend in order to have reassurance they need (30). It may be observed that these patients seek reassurance by frequently administering to emergency departments, running medical tests and establishing "friendship relationships" with physicians (30,43). Many patients with panic disorder ask for help from their friends, families, neighbors and physicians in order to deal with the feelings of insecurity.…”
Section: Discussionsupporting
confidence: 88%
“…Breaks were scheduled from At the end of the day the participants completed a short questionnaire, which included items on how they used the controls, and on their satisfaction with various aspects of the indoor environment. We also collected demographic information, and information on light sensitivity 22 and chronotype, 23 chosen because they might help predict lighting choices. Figure 4 shows data for the prevailing desktop illuminance due to daylight, d E desk .…”
Section: Methodsmentioning
confidence: 99%
“…There were no significant correlations between left LGN volume and mTBI symptom load (SCAT‐5 symptom severity score) at baseline or at 3‐month follow‐up. Due to the known relevance of the LGN in visual processing, correlations between left LGN volume and symptoms of photophobia (using the PAQ scores from the baseline visit and the 3‐month follow‐up visit) 17,27 were also investigated as comparisons. Although individuals with PTH had significantly higher levels of photophobia at baseline compared to healthy controls (PTH: PAQ = 0.29, SD = 0.25; healthy controls: PAQ = 0.09, SD = 0.14; p < 0.001) (see Table 1), no significant correlations were found between left LGN volume and photophobia symptom severity at baseline or 3‐month follow‐up.…”
Section: Resultsmentioning
confidence: 99%